Lack of Association between Recurrent Pregnancy Loss and Inherited Thrombophilia in a Group of Colombian Patients. (11th April 2012) - Cardona, Henry; Castañeda, Serguei A.; Cardona Maya, Wálter; Alvarez, Leonor; Gómez, Joaquín; Gómez, Jorge; Torres, José; Tobón, Luis; Bedoya, Gabriel; Cadavid, Ángela P.
Abstract : Studies have shown an association between recurrent pregnancy loss and inherited thrombophilia in Caucasian populations, but there is insufficient knowledge concerning triethnic populations such as the Colombian. The aim of this study was to evaluate whether inherited thrombophilia is associated with recurrent pregnancy loss. Methods . We conducted a case-control study of 93 patients with recurrent pregnancy loss (cases) and 206 healthy multiparous women (controls) in a Colombian subpopulation. Three single nucleotide polymorphisms (SNPs) markers of the inherited thrombophilias factor V Leiden, prothrombin G20210A, and methylenetetrahydrofolate reductase C677T were genotyped by PCR-RFLP. Activated protein C resistance and plasma levels of antithrombin, protein C, and protein S were also measured. Results . The frequency of thrombophilia-associated SNPs, activated protein C resistance, and anticoagulant protein deficiencies, was low overall, except for the methylenetetrahydrofolate reductase C677T SNP. The differences between patients and controls had no statistical significance. Conclusion . Our study confirms the low prevalence of inherited thrombophilias in non-Caucasian populations and it is unlikely that the tested thrombophilias play a role in the pathogenesis of recurrent pregnancy loss in this Colombian population.